Implementasi Media Audio Visual pada Mata Pelajaran PAI Materi Rasul Allah Idolaku guna Meningkatkan Minat Belajar Peserta Didik - Eni Salafiatin; Shobirin Mukhtar (Action Research Journal, 2022)
The problem that is often encountered in teaching PAI at SDN Medini 1 is the lack of enthusiasm of students towards the material presented by the teacher in lectures. This study aims to determine the effect of the application of audio-visual media on students' interest in learning in PAI subject matter for the Apostle of Allah Idols Class V at SDN Medini 1 Gajah, Demak Regency, in the 2021/2022 academic year. In collecting data in this study using the methods: observation, documentation, and questionnaire. The results of data collection were then analyzed descriptively qualitatively. The results showed that the application of audio-visual media in PAI learning the material of Allah's Apostle Idol was able to increase students' interest in learning. This can be seen from the indicators of interest, namely feelings of pleasure which initially reached 55.22%, increasing to 79.46% in the good category. On the indicator of interest from 56.59% to 79.76% in the good category and on the indicator of enthusiasm for learning which was originally 53.31% changed to 79.76% in the good category.